2020
DOI: 10.1152/japplphysiol.00855.2019
|View full text |Cite
|
Sign up to set email alerts
|

CORP: The use of deuterated water for the measurement of protein synthesis

Abstract: The use of deuterium oxide (D2O) has greatly expanded the scope of what is possible for the measurement of protein synthesis. The greatest asset of D2O labeling is that it facilitates the measurement of synthesis rates over prolonged periods of time from single proteins through integrated tissue-based measurements. Because the ease of administration, the method is amenable for use in a variety of models and conditions. Although the method adheres to the same rules as other isotope methods, the flexibility can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 66 publications
(125 reference statements)
0
32
0
Order By: Relevance
“…Protein synthesis was determined using our established methods. 28 , 34 Briefly, ∼30–50 mg of skeletal muscle tissue was homogenized 1:20 in isolation buffer (100 m m KCl, 40 m m Tris–HCl, 10 m m Tris Base, 5 m m MgCl 2 , 1 m m EDTA, 1 m m ATP, pH = 7.6) with phosphatase and protease inhibitors (HALT, Thermo Fisher Scientific) using a bead homogenizer (Next Advance Inc., Averill Park, NY, USA). After homogenization, subcellular fractions were isolated via differential centrifugation to obtain myofibrillar and collagen protein fractions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Protein synthesis was determined using our established methods. 28 , 34 Briefly, ∼30–50 mg of skeletal muscle tissue was homogenized 1:20 in isolation buffer (100 m m KCl, 40 m m Tris–HCl, 10 m m Tris Base, 5 m m MgCl 2 , 1 m m EDTA, 1 m m ATP, pH = 7.6) with phosphatase and protease inhibitors (HALT, Thermo Fisher Scientific) using a bead homogenizer (Next Advance Inc., Averill Park, NY, USA). After homogenization, subcellular fractions were isolated via differential centrifugation to obtain myofibrillar and collagen protein fractions.…”
Section: Methodsmentioning
confidence: 99%
“…The use of the stable isotope deuterium oxide (D 2 O) has facilitated the capture of slowly turning over proteins because it lends itself to long-term (days to weeks) labeling. 28 The assumptions, limitations, and technical application of the method have been detailed to ensure valid results. 28 When calculating synthesis rates from a single time point, standard tracer methodology assumes that the product undergoes complete renewal (ie, turnover).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it has been recently shown that percentages of 1,6‐hexanediol commonly used to disrupt LLPS impact enzymatic activity, for example, inactivating kinases and phosphatases 36 . It is therefore necessary to develop new probes to selectively change the stability of condensates: since moderate (up to 70%) mole fractions of D 2 O can be tolerated by live cells, 37 for example in studies of the rate of protein synthesis in physiology, 38 analysis of how additions of this co‐solvent influence apparent phase separation phenomena in cells may represent a useful tool in this field.…”
Section: Discussionmentioning
confidence: 99%